STRATEGY FOR SUSTAINABILITY OF PRIVATE HIGHER EDUCATION IN FACING THE ERA OF SOCIETY 5.0 - Supriyatin Supriyatin (Research and Development Journal of Education, 2022)
This study intends to identify and find out the implementation of the sustainability strategy carried out by private universities in Indonesia in facing the era of society 5.0. The purpose of this study is to find out how private universities in Indonesia are preparing for the era of society 5.0. A descriptive qualitative method has been taken for this investigation. The sort of data that was utilized in this investigation was secondary data, which was gathered through the use of the archive technique and was obtained from various publications. The findings of this research led to the identification of nine different approaches to environmental preservation. These approaches are as follows: resource allocation for recycling; environmental issues of product; care of biodiversity; polluting emission into the air, water, and ground; innovation and technology; collaboration; knowledge management; process; and purchase. It is anticipated that this research would be able to provide an overview of the sustainability measures that private colleges in Indonesia have undertaken in order to confront the period of society. 5.0